1996
DOI: 10.1111/j.1600-0536.1996.tb02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritant effects of a detergent in wash, chamber and repeated open application tests

Abstract: Development of irritant contact reactions in a wash test, in a repeated open application test (ROAT) and in chamber tests were compared with each other in 14 atopic and 14 non-atopic Caucasian medical students. In the wash test, the students washed their upper arm skin with 10% dishwashing liquid for 1 min 2 x a day for 1 week. In the ROAT, they applied the same detergent solution to 1 antecubital fossa 2 x daily for 1 week. Chamber tests were performed with the same detergent using 8 mm, 12 mm and 18 mm Finn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…ROAT 7,8 with SLS offers a good simulation of conditions in daily practice as it mimics repetitive and cumulative exposure to environmental irritants and allows the effect of moisturisers on the surfactant‐induced skin irritation and skin repair to be studied. This chronic model appears to represent the clinical situation of irritant contact dermatitis with pronounced skin dryness more closely than the acute irritation model 1 …”
Section: Discussionmentioning
confidence: 99%
“…ROAT 7,8 with SLS offers a good simulation of conditions in daily practice as it mimics repetitive and cumulative exposure to environmental irritants and allows the effect of moisturisers on the surfactant‐induced skin irritation and skin repair to be studied. This chronic model appears to represent the clinical situation of irritant contact dermatitis with pronounced skin dryness more closely than the acute irritation model 1 …”
Section: Discussionmentioning
confidence: 99%
“…found a correlation coefficient of 0·63 between the outcome of a 24‐h patch test and the outcome of a 4‐day repeated 0·5% SLS patch test. In their study on a dish washing liquid, Hannuksela and Hannuksela 9 found poor correlations between acute chamber tests comprising several doses and durations, with an open application test or wash test that were both applied daily over a 1‐week period. Robinson 10 combined the data of two studies, one a 4‐h 20% SLS patch test, and the other a 14‐day repeated SLS patch test with four different concentrations.…”
mentioning
confidence: 99%
“…A disadvantage of the immersion and wash tests is the fact that on the surface of 2 forearms only 2 different agents can be compared. The wash test has the further disadvantage of being less easy to standardize than repeated open exposure or immersion tests (5).…”
mentioning
confidence: 99%